Model Classification Methods in the Treatment of Corneal Ulcers with Mesenchymal Stem Cells - Rafael Souza da Silva; Matheus Cândido Feitosa; Mariza Brandão Palma; Marcelo Weinstein Teixeira; Anísio Francisco Soares (Archives of Current Research International, 2025)
The study was carried out to classify the difficulty in treating corneal ulcers using mesenchymal stem cells as cell therapy. Seven studies were used to carry out the research. It was carried out by the Department of Animal Morphology and Physiology (DMFA) and the Laboratory of Physiology and Experimental Surgery (LAFICE). The research was carried out through a bibliographic survey, highlighting the following topics: routes of application of Mesenchymal Stem Cells (MSCs), tissue origin of MSCs, sex of the animal, species of the animal, depth of the corneal ulcer, comorbidity and time required for re-epithelialization. The results showed that the study that came closest to the set of topics related to increased treatment difficulty took 270 days to recover. The study that came closest to the set of topics related to the least difficulty of treatment took 21 days to recover, demonstrating the efficiency of the proposed classification of difficulty of treatment. The study concludes the efficiency of the method for classifying the difficulty of treating corneal ulcers using mesenchymal stem cells.